2010
DOI: 10.1017/s0025315410000755
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use of humpback whales in Godthaabsfjord, West Greenland, with implications for commercial exploitation

Abstract: North Atlantic humpback whales migrate from breeding grounds to high latitude feeding areas to where individuals display large scale site fidelity. In Godthaabsfjord (Greenland), humpback whales are present from early spring to late autumn. To test for small scale site fidelity and occurrence, identification-photographs were collected from May to September 2007 and 2008 and compared with an older catalogue. We found high small scale site fidelity where 40% of the whales present in 2007 were resighted in 2008. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Whale‐watching activities occur both in the breeding (Avila, Correa, & Parsons, ; Morete, Bisi, & Rosso, ; Schaffar, Madon, Garrigue, & Constantine, ) and the feeding (Boye et al, ) grounds of whales. In the feeding grounds of SEAK, whales feed on abundant prey resources, including: Pacific herring, Clupea pallasii Valenciennes, 1847; capelin, Mallotus villosus (Müller, 1776); and euphasiids, primarily Euphausia pacifica , Hansen, 1911 (Chenoweth, Gabriele, & Hill, ; Dolphin, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whale‐watching activities occur both in the breeding (Avila, Correa, & Parsons, ; Morete, Bisi, & Rosso, ; Schaffar, Madon, Garrigue, & Constantine, ) and the feeding (Boye et al, ) grounds of whales. In the feeding grounds of SEAK, whales feed on abundant prey resources, including: Pacific herring, Clupea pallasii Valenciennes, 1847; capelin, Mallotus villosus (Müller, 1776); and euphasiids, primarily Euphausia pacifica , Hansen, 1911 (Chenoweth, Gabriele, & Hill, ; Dolphin, ).…”
Section: Introductionmentioning
confidence: 99%
“…The recent worldwide growth of whale watching has raised concerns about its effects on targeted cetacean populations (O'Connor, Campbell, Cortez, & Knowles, 2009). These activities can affect cetaceans' habitat use and social cohesion (Boye, Simon, & Madsen, 2010;Nowacek, Wells, & Solow, 2001), and can also acoustically mask their abilities to communicate with sound (Buckstaff, 2004;Scarpaci, Bigger, Corkeron, & Nugegoda, 2000). Short-term effects can consist of the alteration of movement behaviour, such as changes in path linearity (Christiansen, Rasmussen, & Lusseau, 2013a), diving pattern (Gordon, Leaper, Hartley, & Chappell, 1992;Richter, Dawson, & Slooten, 2003), and also respiration rate (Williams, Trites, & Bain, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is worth noting that we did not find evidence for fidelity to specific summer sites, as reported in some whales [51,52], including beluga [53]. If belugas showed site fidelity in the study area, we would have expected significant mean relatedness (R xy ) for the site category.…”
Section: Discussion (A) Social Structure During Migration and Summermentioning
confidence: 56%
“…Oshima et al (2010) found that home ranges of the same species in the Cananéia Estuary, Brazil, also showed great individual variability. Boye et al (2010) showed that although the same humpback whales use the Godthaabsfjord system, West Greenland, as a foraging area year after year, individuals did not remain in the fjord the entire season and the time spent in the fjord was highly variable amongst individuals.…”
mentioning
confidence: 99%